Réponses

Meilleure réponse !
  • carys
  • Modératrice confirmée
2013-03-06T17:58:50+01:00

A = (x + 4) (x + 3)

A = x² + 3x + 4x + 12

A = x² + 7x + 12

 

B = (y + 3) (2y + 8)

B = 2y² + 8y + 6y + 24

B = 2y² + 14y + 24

 

C = (3z + 4) (5 - 6z)

C = 15z - 18z² + 20 - 24z

C = -18z² -9z + 20

 

voilà voilà :)

                                                                                      

2013-03-06T18:01:35+01:00

A=(x+4)(x+3)
A=x²+3x+4x+12
A=x²+7x+12
B=(y+3)(2y+8)
B=2y²+8y+6y+24
B=2y²+14y+24
C=(3z+4)(5-6z)
C=15z-18z²+20-24z
C=-9z-18z²+20